Paralichthys olivaceus MLKL-mediated necroptosis is activated by RIPK1/3 and involved in anti-microbial immunity - Hao, Kangwei; Xu, Hang; Jiang, Shuai; Sun, Li (Frontiers in Immunology, 2024)
Necroptosis is a type of proinflammatory programmed necrosis essential for innate immunity. The receptor interacting protein kinases 1/3 (RIPK1/3) and the substrate mixed lineage kinase domain-like protein (MLKL) are core components of the necroptotic axis. The activation and immunological function of necroptosis in fish remain elusive. Herein, we studied the function and activation of RIPK1/3 (PoRIPK1/3) and MLKL (PoMLKL) in teleost Paralichthys olivaceus. Bacterial infection increased the expression of RIPK1/3 and MLKL. The N-terminal four-helix bundle (4HB) domain of PoMLKL exhibited necroptosis-inducing activity, and the C-terminal pseudokinase domain exerted auto-inhibitory effect on the 4HB domain. PoRIPK3 was capable of phosphorylating the T360/S361 residues in the PoMLKL C-terminal domain and initiated necroptosis, and this necroptosis-inducing activity was enhanced by PoRIPK1. PoRIPK1/3 interacted with PoMLKL in a manner that depended on the RIP homotypic interaction motif (RHIM), and deletion of RHIM from PoRIPK1/3 led to the dissociation of PoRIPK1/3 with PoMLKL. Inhibition of PoMLKL-mediated necroptosis increased Edwardsiella tarda infection in fish cells and tissues, and led to significantly enhanced lethality of the host. Taken together, these results revealed the activation mechanism of PoRIPK1/3-PoMLKL signaling pathway and the immunological function of necroptosis in the immune defense of teleost.